Diffusion of electronic commerce for online purchasing of computer software - Md. Badri, Mohamad Rizal (2001)
Nowadays marketers have to encounter difficulties of getting the edge over competitors given the high competitiveness in the world of Internet shopping or better known as e-commerce. Thus, they always emphasis on the needs to monitor e-commerce purchasing trend. However, in monitoring this trend, they usually ignore the importance of factors that can affect customers' purchasing behavior, especially factors that can influence and attract customers' in e-commerce purchasing. Thus, the main purpose of carrying out this study is to examine the relationship between the diffusion of e-commerce in purchasing computer software and Convenience, Cost, and Knowledge. The findings showed that there is a significant relationship between Convenience, Cost, and the diffusion of e-commerce in purchasing computer software. Internet users put great importance in these two aspects when purchasing via e-commerce. Knowledge however seem to be an significant factor in this study.